Rights, Free Trade, and Politics: The Strategic Use of a Rights Discourse in the Negotiation of Free Trade Agreements (FTAs) - Angelika Rettberg (Colombia Internacional, 2014)
This article seeks to describe the strategic use of a rights discourse by domestic and international actors involved in the negotiation and ratification processes of free trade agreements between Colombia, the United States, and the European Union. We suggest that some of the differences between both FTAs and the processes leading up to their approval and ratification can be attributed to the ability of relevant actors to build and disseminate rights-based arguments in order to develop like-minded political coalitions, and other institutional and contextual characteristics.